THE RELATION OF HYPOSPADIAS TYPES, AGES, AND SURGICAL TECHNIQUES FOR URETHROCUTANEOUS FISTULA COMPLICATION IN CHILD HYPOSPADIAS CASES - Widjajana, Desy Pratiwi; Wahyudi, Septa Surya; Sutejo, Ika Rahmwati (Indonesian Journal of Urology, 2019)
Objective: To find correlation between hypospadias type, age, and surgical technique for urethrocutaneous fistula in child hypospadias cases. Material & Method: This research was an observational analytic research with cross sectional approach. It was conducted at Bina Sehat Jember Hospital, Paru Jember Hospital, and Bhayangkara Bondowoso Hospital. The research samples were hypospadias patients who had done hypospadias repair with susceptible age from 0 months until 16 years. Result: In this study, was found correlation between type of hypospadias with urethrocutaneous fistula (p=0.03 and r=0.43). And the other hand, this research did not find relationship between age at hypospadias surgery with urethrocutaneous fistula complication (p=0.34 and r=0.3). The results of this study indicate that the incidence of urethrocutanoeus fistula complications in the surgery using TIP technique was greater than Onlay Island Flap technique, but in this study, there was no association between hypospadias surgery technique used with complications of uretrocutanoeus fistula (p=0.3 and r=0.22). Conclusion: In this study, there was a significant relationship between hypospadias type with urethrocutaneous fistula complication with statistically moderate strength and positive correlation direction. This study did not show any significant relationship between age and hypospadias surgery technique with complications of urethrocutanoeous fistula.